Desenvolvimento de plantas e produção de óleo essencial de citronela (Cymbopogon winterianus jowitt) sob diferentes adubações - Ucker, Anna Paula Ferreira Batista Goldfeld (2013)
The Citronella Grass currently has excelled in domestic and foreign markets, due to its medicinal properties. The use of the essential oil is increasing, there are several functions, commonly used in the pharmaceutical industry, in agronomic practices (with adoption of conservation methods), used as insecticides, fungicides, in the area of veterinary as ticks and cleaning as disinfectants. The expectation for those who produce the oil is economically viable use your directing for family farmers which can add value to their properties and generate income. It is a little known plant, disclosed and addressed. Given this gap, was aim to work with citronella to evaluate performance in the treatments used, oil yield and seedling production. The challenge of this work is to bring information about the culture, cultivation and their purposes. In the study we evaluated various treatments with organic manure, mineral NPK and control, evaluating oil yield, fresh weight, dry weight, diameter, plant height after cutting. The experimental design was randomized with four replications. In organic treatments which got the biggest highlight was with 0.5 liter of organic fertilizer from fresh cattle manure, which was applied in each pit parcels worked. For the conditions of the State of Goiás plant development ensued in a very adaptable, demonstrating hardiness of the plant, and how it can be profitable for the producer of small income.